KEHAMILAN HETEROTOPIK DENGAN SYOK HIPOVOLEMIK – SEBUAH LAPORAN KASUS - Putra, Novitrian Eka; Damayanti, Marshavina (Tirtayasa Medical Journal, 2025)
Heterotropic pregnancy is refers to the coexistence of multifetus pregnancy in intrauterine and extrauterine simultaneously. It is a rare and life-threatening condition. The risks of heterotropic pregnancy accounts for 1 per 30.000 from natural conception. This case report presents a case of first trimester pregnancy diagnosed by Transabdominal Ultrasound with Culdocentesis technique and underwent salpingectomy procedure successfully. A 33 years old, multigravida with history of abortion lady at 9 weeks period of gestation was presented to the Maternity Emergency Room, at Banten Regional Public Hospital, by increasing abdominal pain for 4 days and nausea episodes with the presence of Chandelier Sign. Transabdominal ultrasound revealed a left adnexal mass at fallopian tube and presence of gestational sac intrauterine. Upon the examination, patient was hemodynamically unstable, tender on palpation and diffusely distended. The patient’s final diagnosis was 9 weeks heterotropic pregnancy with a live intrauterine fetus and rupture left ectopic pregnancy. Patient underwent an emergency laparotomy with salpingectomy procedure for presumed ruptured tubal ectopic pregnancy. Earlier time to diagnose rupture ectopic pregnancy gives a good maternal outcome and hence crucial in the management.